Analysis on Hiemenz flow over a shrinking sheet in hybrid nanofluid - Ibrahim, Muhammad Hafiezul Ridhwan; Fazlina Aman, (Enhanced Knowledge in Sciences and Technology, 2022)
The Hiemenz flow of hybrid nanofluid across a shrinking sheet is investigated in this paper. The similarity equations are created using similarity variables and then solved in Maple software using the shooting technique with RKF45 method. The effect of several governing parameters such as shrinking parameter and nanoparticles volume fraction for alumina oxide and copper on the flow behavior is examined and are depicted in table and graphs. It is found that both heat transfer rate and the skin friction on the surface escalated as cooper nanoparticles volume fraction increased. The opposite behavior is observed for alumina oxide nanoparticle volume fraction. Meanwhile, the velocity profiles decrease but the temperature profiles increase with shrinking parameter for fixed value of both copper and alumina nanoparticles volume fraction.